Association of anti‐RNA polymerase III antibody and malignancy in Japanese patients with systemic sclerosis. Issue 5 (27th February 2015) - Saigusa, Ryosuke; Asano, Yoshihide; Nakamura, Kouki; Miura, Shunsuke; Ichimura, Yohei; Takahashi, Takehiro; Toyama, Tetsuo; Taniguchi, Takashi; Noda, Shinji; Aozasa, Naohiko; Akamata, Kaname; Sumida, Hayakazu; et al.
Abstract: Patients with systemic sclerosis (SSc) have an increased risk of malignancy compared with the general population. Recently, SSc patients with anti‐RNA polymerase III antibody have been reported to have an increased risk of malignancy as compared with those with other disease‐specific autoantibodies in US, European and Australian populations. Therefore, we studied the relationship between disease‐specific autoantibodies and malignancy in 261 Japanese SSc patients. The prevalence of malignancy was significantly higher in patients with anti‐RNA polymerase III antibody (7/22, 31.8%) than in those with anti‐topoisomerase I antibody (2/82, 2.4%) and in those with anticentromere antibody (8/137, 5.8%). Importantly, among seven patients with anti‐RNA polymerase III antibody and malignancy, three patients (42.9%) developed malignancy from 6 months before to 12 months after SSc onset. Thus, malignancy complication in Japanese SSc patients with anti‐RNA polymerase III antibody is as high as that in other races, suggesting that SSc patients with anti‐RNA polymerase III antibody share the same pathological process among different ethnic groups.